Natural and anthropogenic influences on recent sediment characteristics in the Knysna Estuary, South Africa and Yangtze River Estuary, China - Dubazana, Yakhuluntu (Department of Environmental and Geographical Science, 2023)
Estuaries and tidal wetlands situated at the nexus of fluvial, marine and terrestrial conditions is highly dynamic and complex system. Despite strong hydrodynamics, estuarine tidal flats are preferential sites for the accumulation of fine-grained sediment, organic matter and metals from various marine and terrestrial sources including those of natural and anthropogenic origin. The coastal zone performs many key ecosystem service functions for sustainable development, thus making them valuable ecological entities. In this study, the Chongming Island tidal flats of the Yangtze River Estuary in China and the Knysna Estuary in South Africa are selected as case studies. The objective of this study is to investigate the recent distribution and abundance of sediment characteristics, organic matter, and modern major and trace elements in sediments through space and time. Physically speaking, the two estuaries are very different. Three sediment cores taken from the Knysna Estuary and two sediment cores taken from the Chongming Island of the Yangtze River Estuary in 2019 were analysed to document grain size distribution using Malvern Mastersizer, geochemical signatures including major elements (Al, Fe, K, Ti, and Ca) and trace elements (Ni, Cr, Mn, Sr, Rb, Cu, Pb, Zn and Zr) via XRF, loss-on-ignition and magnetic susceptibility. The cores were divided into three zones based on the approximated time periods. Our results show that the introduction of European land-use and human impacts in the Knysna Estuary resulted in an increase in SARs to be at least three times higher than pre-European SAR values. The widespread deforestation coupled with intense farming exerted significant controls on the quantity of sediment transported downstream and increased erosion within the Knysna Estuary. Agriculture intensification increased the terrigenous input of Al, K, Ca, Ti and Cu levels. In Unit I (ca. 1960s-Present), the heavy metals Fe, Mn, Pb, Zn and Cu escalated in concentration indicating anthropogenic input due to urbanization and infrastructure development in the Knysna Estuary. In Chongming Island, Mg, Al, K, Ti, Mn, Fe, Cu, Zn, Rb, Pb and magnetic susceptibility values in the cores all show increasing trends relative to the pre-1950s and post 2002 units. This is consistent with the significantly increasing trends in the total energy consumption for the industrial development in China and the heavy metal input from the Yangtze River. Post 2002 (Unit I), the same elements exhibited a decreasing trend and their mean concentrations (mg kg-1) is the lowest of all the three units. This is attributed to the improvement in environmental protections and regulatory control of atmospheric pollution and a shift in the consumption of energy from the industrial period in the 1950s to 2000s. Coastal zone research tend to view estuaries and tidal wetlands as an independent and isolated system from any global estuary. A benchmarking case study would provide the opportunity to examine coherence, differences and similarity of coastal behavior across two different biographic regions.